(3OhQ GdbWGY GdRQGYj aj OYe GdJHGOd GdJLGQj Hjf eUQ hGdShOGf aj EWGQ GfaUGd GdLfhH (B/ s - (3CMeO eMeO eMeO MSjfs; (3SGej GdSjO (B: s ((3GdbGgQI (B: s (3CMeO eMeO eMeO MSjf (B: s, 2014)
(3JgOa GdOQGSI Gdi HMK h JMdjd OhQ GdbWGY GdRQGYj aj OYe GdJHGOd GdJLGQj Hjf eUQ h GdShOGf aj EWGQ GfaUGd GdLfhH (B: (3MjK JeMhQJ ETcGdjI GdOQGSI Mhd JSGDd QFjSi h gh eG JCKjQ GfaUGd GdLfhH Ydi OhdI GdShOGf (B: (3h Gdi Ci eOi jecf Cf jSGge GdbWGY GdRQGYi ai JOYje GdJHGOd GdJLGQi Hjf cd ef eUQ h GdShOGf? h ai SHjd GdELGHI Yf gPG GdJSGDd GSJNOeJ GdOQGSI cdG ef GdefgL GdhUai GdJMdjdi h GdefgL GdGSJfHGWi (B. (3h JhUdJ GdOQGSI Gdi YOO ef GdfJGFL CHQRgG (B: (3GdJTGHg ai GdaLhI GdZPGFjI deUQ h GdShOGf COi Gdi VYa GdJHGOd GdJLGQi Hjf GdHdOjf ai GdSdY GdRQGYjIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdEbJUGO h GdYdhe GdSjGSjI (B- (3bSe GdGbJUGOs
(3UOQ GjVG cbQU eOeLs
Keywords: (3CKQ GfaUGd GdLfhHs; (3GdbWGY GdRQGYjs; (3ebheGJ GdbWGY GdRQGYjs